WORD GAMES AS AN EFFECTIVE WAY OF TEACHING ENGLISH FOR ESL LEARNERS - Zarnigor Sunatova, Dilnoza Chariyeva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This research examines the use of word games as an innovative and effective approach to teaching English to ESL students. It emphasizes the rising global necessity for English proficiency and points out the limitations of traditional, teacher centered methodologies. Through the application of activities like Hangman, Word Ladder, Chain Story, Pictionary, Word Associations, and Kahoot, the study reveals notable advancements in learners’ language accuracy, vocabulary knowledge, creative thinking, mental flexibility, and overall enthusiasm for learning. The outcomes suggest that incorporating interactive word games into lessons not only enriches the language acquisition process but also fosters critical thinking and collaboration among students. Ultimately, the study highlights word games as a highly beneficial pedagogical strategy for improving ESL education.